RSA Public Key Cryptography Encryption and Decryption Technique Involving Pythagorean Prime Numbers - Janaki , G.; Sangeetha , P. (Explorations in Diophantine Equations, 2023)
In this communication, we have attempted to apply the idea of encryption and decryption using RSA public key cryptography in number theory to the problem of Pythagorean Prime.